2015
DOI: 10.1371/journal.pone.0118668
|View full text |Cite
|
Sign up to set email alerts
|

Non-Protein Coding RNA Genes as the Novel Diagnostic Markers for the Discrimination of Salmonella Species Using PCR

Abstract: Salmonellosis, a communicable disease caused by members of the Salmonella species, transmitted to humans through contaminated food or water. It is of paramount importance, to generate accurate detection methods for discriminating the various Salmonella species that cause severe infection in humans, including S. Typhi and S. Paratyphi A. Here, we formulated a strategy of detection and differentiation of salmonellosis by a multiplex polymerase chain reaction assay using S. Typhi non-protein coding RNA (sRNA) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
1
11
1
Order By: Relevance
“…That most of the Salmonella genomes are nicely clustered according to their serotype in Figure 7 is surprising, as the nonprotein coding sRNA genes analyzed here do not have a speciic role in expression of surface antigens. The correlation identiied here is in line with a publication that sRNA genes can be used as targets for serotype-speciic PCR detection of Typhi and Paratyphi [23]. It was recently described that some sRNA genes of S. Typhimurium are under regulation of Sigma 28, and there is extensive cross talk between genes of the Salmonella pathogenicity pathways SPI1 and SPI2 and particular sRNA genes [24].…”
Section: Conserved Rnas Across 201 Salmonella Genomessupporting
confidence: 85%
“…That most of the Salmonella genomes are nicely clustered according to their serotype in Figure 7 is surprising, as the nonprotein coding sRNA genes analyzed here do not have a speciic role in expression of surface antigens. The correlation identiied here is in line with a publication that sRNA genes can be used as targets for serotype-speciic PCR detection of Typhi and Paratyphi [23]. It was recently described that some sRNA genes of S. Typhimurium are under regulation of Sigma 28, and there is extensive cross talk between genes of the Salmonella pathogenicity pathways SPI1 and SPI2 and particular sRNA genes [24].…”
Section: Conserved Rnas Across 201 Salmonella Genomessupporting
confidence: 85%
“…The target fragment was amplified at concentrations of 58.5 ng/μL to 5.85 pg/μL DNA ( Figure 3A ). The results suggested that at least 5.85 pg/μL of genomic DNA was required for detection of S. Pullorum using this assay, which was slightly lower than previous studies (10 pg/μL) using Salmonella genomic DNA (Nithya et al, 2015). On the other hand, a 10-fold serial dilution of S. Pullorum cells that ranged from 10 4 CFU to 10 -1 CFU per PCR system was evaluated.…”
Section: Resultscontrasting
confidence: 54%
“…In current study, StyR-36 gene was amplified in 40 samples showing 68.97% amplification results. Nithya et al (2015) conducted a study on Salmonella species by targeting StyR-3, StyR-36 and StyR-143 genes in order to evaluate the specificity of genes in S. paratyphi and S. typhi. StyR-3 and StyR-46 was found in both the species while StyR-36 was amplified only in S. typhi.…”
Section: Resultsmentioning
confidence: 99%
“…Extracted gDNA was confirmed on 1% agarose gel and qualitatively and quantitatively analyzed using spectrophotometer (HP 8451A Diode Array Spectrophotometer, USA). Two pair of primers, i-e, ST1/ST2 (5'-TATGCCGCT ACATATGATGAG-3', 5'-TTAACGCAGT AAAGAGAG-3') and StyR-36F/StyR-36R (5'-TGCCATGTAATCGGACGCCGAC-3', 5'-AGCCAACAAACGCGGTTGCG-3') were used to amplify 498 bp of flagellin and 204 bp of StyR-36 gene (Haque et al, 1999;Nithya et al, 2015), respectively. Amplification of respective genes was carried out using PCR Sprint Thermal Cycler (Thermo Electron Corporation, USA).…”
Section: Dna Extraction and Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
See 1 more Smart Citation